ADVANCING LEARNER AUTONOMY IN FOREIGN LANGUAGE EDUCATION THROUGH CONTEMPORARY METHODS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
. The concept of autonomy in foreign language learning has gained prominence in recent decades as educators recognize its importance in achieving sustainable and meaningful language acquisition. This article explores how modern methods-such as flipped classrooms, blended learning, gamification, and learner self-assessment-contribute to the development of learner autonomy. Drawing on recent pedagogical research and expert opinions, the study highlights practical techniques and theoretical frameworks for fostering independent language learners.